HUKUM ISLAM, DEMOKRASI DAN HAK ASASI MANUSIA - Eva Iryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Islam has a strong legal foundation, the Al-Quran is one of them. Democracy is often defined as respect for human rights, participation in decision-making and equality before the law. From then appear idioms democracy, as egalite (equation), equality (justice), liberty (freedom), human rights (human rights), and so on. Human Rights has been established in the Koran.  is also regulated under the laws in every country.  is run by the existing rules.Keyword : Islamic law, democracy, human rights